Pergerakan kurs spot dan kurs forward pada future spot - Ana Fauziah; Renea Shinta Aminda; Supramono Supramono (Universitas Darussalam Gontor, 2020)
The purpose of this research are to determine the movement of the spot rate on the future spot, the movement of the forward rate on the future spot, the movement of the spot rate and the forward rate on the future spot. This research uses two quarters, that is quarter I to quarter II of 2019. This research uses regression models for the forecasting method. The variables are the spot rate, forward rate, and future spot. Samples were obtained from BI. The regression model was tested using the classical assumption test. The results of the data analysis show that the spot rate has a significant movement on the future spot, this is evidenced by the regression coefficient value of -2.9938 and a probability value of 0.0042. The forward exchange rate also shows the results of significant movements on the future spot, as evidenced by the regression coefficient value of -2.9581 and a probability value of 0.0046. The spot rate and forward rate together have an effect on the future spot, as evidenced by the results of statistical analysis with an F-Statistical value of 5.5895 and an F-Statistical probability value of 0.0063.